Police use-of-force self-efficacy: an antidote to the Ferguson effect? - Marier, Christopher J. (Journal of crime and justice, 2024)
Research has consistently shown that officers’ perceptions of deteriorated relationships with the public are associated with physical and emotional disengagement with their work. Anecdotal evidence suggests that this ‘Ferguson Effect’ has also contributed to reluctance to use necessary physical force in the course of their duties, leading to compromises for officer safety and public safety. This study has two objectives: first, it is the only study to systematically assess the claim that apprehensiveness to use force is associated with perceptions of community support; second, it examines whether use-of-force self-efficacy reduces apprehensiveness to use force. Using OLS regression of officer surveys from 4,000 police officers in a Southeastern U.S. state, we find support for both hypotheses, as well as evidence of interaction effects. We identify several practical implications for agency leaders, and further encourage the development of use-of-force self-efficacy as a substantively and theoretically meaningful concept for researchers.